DAKWAH BY THE PEN: SALIM A. FILLAH’S AUTHORITY IN PRO U MEDIA - Siti Mupida; Khoirin Nisai Shalihati (IAIN Salatiga, 2019)
This article discusses ‘dakwah’ (Islamic missionary work) with a friendly concept using rhetoric and narratives that are easily understood by various groups. The missionary work message is covered with beautiful rhetoric by Salim A. Fillah through his books published by Pro U Media. This study uses normative juridical approach with descriptive study. Data collection is condcuted by literature study. The collected data then analyzed qualitatively through deductive method. The findings of the study show that the new Islamic literature has been popularized by young Muslim writers affiliated with contemporary Islamic movements such as Hizbut-Tahrir Indonesia (HTI), Salafi, and Tarbiyah. This research shows that Indonesian Islamic thinker like Salim A. Fillah through social media and his published books uses various scientific arguments based on some classical and modern literature. Formerly Salim A. Fillah is not a person who has ever studied at pesantren (Islamic boarding school) but his religious view can be seen in his fatwas (religious advices) which affecting various communities